CataractAsist: Convolutional Neural Network-Based Early Detection System for Cataracts - Ranov, Nazhif Teggar; Priambodo, Rinto (Politeknik Ganesha Medan, 2026)
Cataract disease is one of the leading causes of blindness worldwide, especially in developing countries with limited access to healthcare facilities. To address this challenge, this study aims to develop an automated cataract detection system using the Convolutional Neural Network (CNN) method. This system is designed to classify eye images into three classes, namely Normal, Mature, and Immature, by utilizing the